Nomi di varietà di uve da una raccolta ampelografica ottocentesca (Carte Romanze, 2022)
The contribution aims to deepen the study of the Italian wine lexicon, with particular reference to ampelonymy. A corpus of denominations of varieties and sub-varieties of grapes was created, coming from an ampelography of the early nineteenth century, which were analyzed from a morpho-syntactic, semantic-motivational and variational point of view.